The Reality of Kindergarten Teachers using Smart Boards to Develop Health Awareness in Children - Youssef, Fayza Ahmed Ali; Hammam, Fatima Hamad M (Journal of Cultural Analysis and Social Change, 2025)
The current study aims to identify the extent to which kindergarten teachers use interactive whiteboards to develop children's health awareness. The descriptive approach was used, and the study was conducted with (100) kindergarten teachers registered in government kindergartens in Najran. The following instruments were used in the study: - A questionnaire to measure the extent to which kindergarten teachers use interactive whiteboards to develop children's health awareness, which included the following sections: (the extent to which kindergarten teachers use interactive whiteboards to develop children's health awareness - obstacles to kindergarten teachers using interactive whiteboards to develop children's health awareness). The results of the study indicate a weak extent to which kindergarten teachers in Najran use interactive whiteboards to develop children's health awareness, as the arithmetic mean for the section was (2.42), which is a low average on a five-point scale, reflecting the limited implementation of this educational tool in classrooms. It can be concluded that the use of smart boards – despite their availability – remains below the required level to achieve educational goals related to developing children's health knowledge. Conversely, the axis of obstacles to using smart boards received a high average score of (4.21), indicating that teachers face significant difficulties hindering the application of technology in classroom practices. Based on the study's findings, the researchers offered several recommendations: Conducting specialized training programs for kindergarten teachers in the use of smart boards and the production of interactive health content for children; providing technical support and suitable technological infrastructure within kindergartens to ensure uninterrupted and easy use; developing educational guides that include digital health activities applicable via smart boards; encouraging teachers to share successful experiences and highlight outstanding practices to promote effective usage models; and promoting partnerships between kindergartens and health authorities to produce targeted and simplified digital health content for children.